Development in Modern Africa - Shanguhyia, Martin S. (London)
1 online resource (249 p.).
Keywords: Development in Modern Africa: Past and Present Perspectives contributes to our understanding of Africa's experiences with the development process. It does so by adopting a historical and contemporary analysis of this experience. The book is set within the context of critiques on development in Africa that have yielded two general categories of analysis: skepticism and pessimism. While not overlooking the shortcomings of development, the themes in the book express an optimistic view of Africa's development experiences, highlighting elements that can be tapped into to enhance the condition of African populations and their states. By using case studies from precolonial, colonial, and postcolonial Africa, contributors to the volume demonstrate that human instincts to improve material, social and spiritual words are universal. They are not limited to the Western world,which the term and process of developmentare typically associated with. Before and after contact with the West, Africans have actively created institutions and values that they have actively employed to improve individual and community lives. This innovative spirit has motivated Africans to integrate or experiment with new values and structures, challenges, and solutions to human welfare that resulted from contact with colonialism and the postcolonial global community. The book will be of interest to academics in the fields of history, African studies, and regional studies.